2006
DOI: 10.1007/s10488-006-0091-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of “Dual Focus” Mutual Aid on Self-Efficacy for Recovery and Quality of Life

Abstract: Four million adults in the U.S. have co-occurring serious mental illness and a substance use disorder. Mutual aid can usefully complement treatment, but people with co-occurring disorders often encounter a lack of empathy and acceptance in traditional mutual aid groups. Double Trouble in Recovery (DTR) is a dual focus fellowship whose mission is to bring the benefits of mutual aid to persons with dual diagnoses. Three hundred and ten persons attending 24 DTR groups in New York City during 1998 were interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Recovery involves the development of new meaning and purpose in one's life as one grows beyond the catastrophic effects of mental illness.'' Drawing from the principles utilized in addiction recovery, the mental health community recognized that there are multiple outcomes associated with mental health and one could certainly move beyond just stability (Harding et al 1987;Magura et al 2007;Sullivan 1997).…”
Section: Recoverymentioning
confidence: 99%
“…Recovery involves the development of new meaning and purpose in one's life as one grows beyond the catastrophic effects of mental illness.'' Drawing from the principles utilized in addiction recovery, the mental health community recognized that there are multiple outcomes associated with mental health and one could certainly move beyond just stability (Harding et al 1987;Magura et al 2007;Sullivan 1997).…”
Section: Recoverymentioning
confidence: 99%
“…As a consequence of this, however, a further potential barrier to AA participation by DDIs is AA members' potential uncertainty and confusion about which psychiatric symptoms lie along a typical developmental course of alcoholism recovery, and, thus, are likely to respond to application of the 12 steps and AA group support and which may require professional intervention. Perhaps for reasons of perceived group unity and cohesion, AA attendees who are overly focused on the topic of mental illness and frequently talk about it at meetings may be viewed as broaching issues that lie outside of the realm of AA's intended purpose and may be implicitly or explicitly discouraged from talking about it by other members (Bogenschutz & Akin, 2000;Magura, Cleland, Vogel, Knight, & Laudet, 2007).…”
Section: The Focus On Issues Besides Substance Usementioning
confidence: 99%
“…A single research group has used a prospective, longitudinal design to study participation outcomes in a sample of approximately 300 DTR members in 24 groups in New York City (Laudet et al, 2000a;Laudet et al, 2000b;Laudet, Cleland, Magura, Vogel, & Knight, 2004;Laudet, Magura, Cleland, Vogel, & Knight, 2003;Magura et al, 2007;Magura, Laudet, Mahmood, Rosenblum, & Knight, 2002;.…”
Section: Research On Dual Diagnosis Mutual-help Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research on the effectiveness of DTR among mainly long-term members demonstrated that DTR affiliation was associated with increased abstinence from drugs/alcohol (Laudet et al, 2004), better psychiatric medication adherence (Magura et al, 2002), and improved coping and quality of life (Magura, Cleland, Vogel, Knight, & Laudet, 2007). Specific self-help processes in DTR groups - helping others and mutual learning - were associated with a higher rate of abstinence (Magura et al, 2003).…”
Section: Introductionmentioning
confidence: 99%